2021
DOI: 10.3389/fpls.2021.644218
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus Interplay in Lupin Root Nodules and Cluster Roots

Abstract: Nitrogen (N) and phosphorus (P) are two major plant nutrients, and their deficiencies often limit plant growth and crop yield. The uptakes of N or P affect each other, and consequently, understanding N–P interactions is fundamental. Their signaling mechanisms have been studied mostly separately, and integrating N–P interactive regulation is becoming the aim of some recent works. Lupins are singular plants, as, under N and P deficiencies, they are capable to develop new organs, the N2-fixing symbiotic nodules, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 115 publications
(128 reference statements)
0
30
0
1
Order By: Relevance
“…More importantly, the effect of N-deficiency is less important for plants under P-deficiency. Recently, Pueyo et al (2021) reported structural and functional modifications in roots, leading to the formation of clusters and altered FIGURE 1 | Schematic representation of nitrogen-starvation response and phosphate-starvation responses explaining N/P interactions. PHR1 acts as a major transcriptional regulator of P-starvation response, which is accompanied by the activation of phosphate starvation-induced (PSI) genes followed by phosphate uptake and translocation by phosphate transporters (PHO1 and PHT1s).…”
Section: Interaction Between N and P Homeostasis In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, the effect of N-deficiency is less important for plants under P-deficiency. Recently, Pueyo et al (2021) reported structural and functional modifications in roots, leading to the formation of clusters and altered FIGURE 1 | Schematic representation of nitrogen-starvation response and phosphate-starvation responses explaining N/P interactions. PHR1 acts as a major transcriptional regulator of P-starvation response, which is accompanied by the activation of phosphate starvation-induced (PSI) genes followed by phosphate uptake and translocation by phosphate transporters (PHO1 and PHT1s).…”
Section: Interaction Between N and P Homeostasis In Plantsmentioning
confidence: 99%
“…More importantly, the effect of N-deficiency is less important for plants under P-deficiency. Recently, Pueyo et al (2021) reported structural and functional modifications in roots, leading to the formation of clusters and altered nodule metabolism, under P and N deficiencies. Signaling factors, including phytohormones and miRNAs, were reported to be the important players in the N and P interactions.…”
Section: Interaction Between N and P Homeostasis In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the reviews; one is related to interactions between two essential elements, S and Fe (Astolfi et al, 2021); two are related to interactions between macro-and micro-nutrients (Fan et al, 2021;Kumar et al, 2021); and the other two are dedicated to interactions between beneficial elements, Si and Se, and essential ones (Pavlovic et al, 2021;Zhou et al). The minireview deals with the interaction between N and P in the development of root nodules and cluster roots (Pueyo et al, 2021). The perspective article is devoted to describing new approaches based on computational analysis to predict interactions between proteins related to different elements (Di Silvestre et al).…”
Section: Editorial On the Research Topic Nutrient Interactions In Plantsmentioning
confidence: 99%
“…This increase in root exudation surface enhances nutrient mobilization in the rhizosphere [26,30]. Nodules and cluster roots have major roles in lupin N and P metabolisms, respectively, but there are interactive regulation pathways between both organs that interlink N and P recycling [33].…”
Section: Introductionmentioning
confidence: 99%